Ewing Sarkoma: Ulasan Singkat Keganasan: Indonesia - Rafi Gutra Aslam; Helmi Ismunandar; Risal Wintoko; Exsa Hadibrata; Anisa Nuraisa Jausal (CV. Jasa Sukses Abadi, 2023)
A malignancy that identified first by James Ewing in 1921. Ewing sarcoma is a malignancy of the bones caused by abnormal activity of progenitor cell mesenchymal occurs by a genetic factor where the patient had a combination of translocation chromosome non-random in t(11; 22) (q24;q12) or t(21; 22) (q22; q12). The patient will have pathognomonic findings of periosteal reaction similar to